Theme and thematic progression of Malaysian higher education advertorials / Nurul Amilin binti Abu Talib - Abu Talib, Nurul Amilin (2014)
Systemic Functional Grammar is an approach which has been applied in numerous fields and genres (Thompson, 1996; Bloor & Bloor, 2004) and is considered a significant tool in exploring different discourses (Fairclough, 2001; Bloor & Bloor, 2004). The textual metafunction, especially, is useful as it organises meaning and message in a cohesive manner. Hence, the main objective of this study is to look at the types of theme and thematic progression patterns found in the Malaysian advertorials of higher education. In this study, the Unmarked topical theme consisting of noun phrases was found to be the most prominent theme type. The reason may be that it is the most common method of introducing information to readers in order to lead to persuasion. Additionally, the advertorials applied a high occurrence of constant theme patterns and linear theme patterns, with a slightly higher occurrence of constant theme pattern. The use of the constant theme patterns is to enable the readers to focus on a specific element (i.e. the institution, courses offered, etc.) and to follow the development of the text.